2001
DOI: 10.1111/j.1778-428x.2001.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Strategies to Decrease Excessive Blood Loss in Cardiac Surgery: Meta‐analysis of Clinically Relevant Endpoints*

Abstract: SUMMARY Background: Excessive bleeding may complicate cardiac surgery, and is associated with increased morbidity and mortality. Pharmacological strategies to decrease perioperative bleeding have been investigated in a large number of controlled trials, most of which have shown a decrease in blood loss. However, most studies lacked sufficient power to detect a beneficial effect on clinically more relevant outcomes. We did a meta‐analysis of all randomized, controlled trials of the three most frequently used p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
10

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 100 publications
(59 reference statements)
2
98
0
10
Order By: Relevance
“…In 1997, Laupacis and Fergusson [53] published another metaanalysis showing that desmopressin was ineffective in reducing blood loss in cardiac surgery. Another metaanalysis of randomized controlled trials studying the role of desmopressin in cardiac surgery was per- formed by Levi et al [54] in 1999, in which the use of desmopressin resulted in a small decrease in perioperative blood loss but was not associated with a beneficial effect on other clinical outcomes (mortality, repeat thoracotomy, proportion of patients receiving transfusion). Moreover, desmopressin was associated with a 2.4-fold increase in the risk of myocardial infarction.…”
Section: Desmopressin In Patients Without Preexisting Bleeding Disordersmentioning
confidence: 99%
“…In 1997, Laupacis and Fergusson [53] published another metaanalysis showing that desmopressin was ineffective in reducing blood loss in cardiac surgery. Another metaanalysis of randomized controlled trials studying the role of desmopressin in cardiac surgery was per- formed by Levi et al [54] in 1999, in which the use of desmopressin resulted in a small decrease in perioperative blood loss but was not associated with a beneficial effect on other clinical outcomes (mortality, repeat thoracotomy, proportion of patients receiving transfusion). Moreover, desmopressin was associated with a 2.4-fold increase in the risk of myocardial infarction.…”
Section: Desmopressin In Patients Without Preexisting Bleeding Disordersmentioning
confidence: 99%
“…However, despite of this tendency, in-hospital mortality in this meta-analysis was always lower in the aprotinin group. Comparing patients who received aprotinin, regardless of the dose, with the placebo group, the in-hospital mortality was twice as high in the placebo group 82 . It is important to stress that the scientific value of the mortality evaluation would be higher if the follow-up were not restricted to the hospitalization period.…”
Section: Discussionmentioning
confidence: 98%
“…In another meta-analysis, undertaken by Levi et al 35 , comparing TA and EACA together, as lysine analogues, to placebo, demonstrated a tendency for decreased prevalence of MI in the group treated with lysine analogues than in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations